PERSEPSI GURU TERHADAP PELAKSANAAN SUPERVISI OLEH KEPALA SEKOLAH MENENGAH ATAS NEGERI (SMAN) DI KECAMATAN SIJUNJUNG - Gusria Herlina (Universitas Negeri Padang, 2013)
The goal of this research are to see information about perception of teachers on the implementation of supervision . This type of descriptive research study. The population is 98 teachers and the sample is 52 people that taken by Stratified Proportional Random Sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score . The result of this research are the perception of teachers on the implementation of supervision by the headmaster in SMAN District of Sijunjung stay in quite accomplished category. Key word : Perception of teachers on the implementation of supervision.